Culture media affect follicle survival and oocyte maturation in preantral mouse follicle cultures - Nonowaki, S., Prefectural Univ. of Hiroshima (Japan); Takahashi, K; Horiuchi, T (Journal of mammalian ova research, 2010)
To investigate the effect of media on mouse follicular development and oocyte maturation in vitro, we compared eight culture media. Early preantral follicles were mechanically dissected from the ovaries of 14-day-old mice and cultured for 10 days. The tested media were: alpha-MEM, D-MEM/F-12, D-MEM with high glucose (4.5 g/L) (D-MEM[H]) or low glucose (1 g/L) (D-MEM[L]), Waymouth, M199, IMDM, and RPMI1640. All of the media were supplemented with 5% FBS, ITS, 100 mlU/ml rhFSH, 1 mlU/ml rhLH and, 0.5% gentamicin. Compared to the other media (P 0.05), a higher percentage of follicles survived and antral-like cavity formation was seen after 10 days of culture when the follicles were cultured in alpha-MEM, Waymouth, D-MEM/F-12, or D-MEM(L). Among the four media with higher follicle survival, the oocyte diameter on day 10 of culture was largest in alpha-MEM and smallest in Waymouth. The highest percentages of MII oocytes were obtained when follicles were cultured in alpha-MEM, D-MEM(L), and D-MEM/F-12. In contrast, in Waymouth, no MII oocytes were obtained. The media used for mouse preantral follicle growth in vitro affected follicle survival and oocyte maturation. Of the media that we tested, alpha-MEM, D-MEM(L), and D-MEM/F-12 were superior for mouse preantral follicle cultures.